Futures trading and supply contracting in the oil refining industry - Sykuta, Michael E. (Journal of Corporate Finance, 1996)
This paper examines the relation between commodity futures trading and the real side contracting behavior of firms dealing in the commodity. I argue that futures serve as a flexible form of physical contracting and should be examined in the context of the firm's contracting activities, and not strictly in the context of its financial activities. Data from an oil refining company are used to empirically study this relation. The results are consistent with a contracting view of futures use and appear inconsistent with implications of hedging theories.